Configurational and Coactivational Views of Organizational Structure - Dow, Gregory K. (Academy of Management Review, 1988)
Two distinct views of organizational structure, configurational and coactivational, are discussed. The configurational view stresses the authoritative coordination of work, whereas the coactivational view emphasizes recurrent patterns of interaction among participants. These two conceptual schemes differ in their stances toward hierarchy, power, and organizational purposiveness. The coactivational view substitutes “invisible hand” explanations of structure for the intentionalist explanations advanced by configurational theory.